2004
DOI: 10.2116/analsci.20.1389
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Metal Binding Properties of Rhamnogalacturonan II from Plant Cell Walls by Size-Exclusion HPLC/ICP-MS

Abstract: IntroductionRhamnogalacturonan II (RG-II) is a structurally complex pectic polysaccharide isolated from vascular plant cell walls, and is composed of a backbone of galacturonic acid (GalA) residues and four side chains of diverse glycosyl residues (Fig. 1). 1,2 RG-II is one of the most complex polysaccharides identified so far; however, its function remained unclear for many years. Recently, a dimeric RG-II-borate complex (dRG-II-B) in which a borate-diol ester (1:2) cross-links two monomeric RG-II (mRG-II) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…One of probable mechanisms accounting for the activating effect of boric acid on HM removal from the soil by plants is that boron is involved in complexation with carbohydrate derivatives, pectin and rhamnoga lacturonan II, in the cell wall (Kobayashi, Matoh, and Junichi, 1996;O'Neill et al, 1996), with the resulting complexes also including metal ions such as Ca 2+ , Sr 2+ , Ba 2+ , Pb 2+ , and La 3+ (Matsunaga and Ishii, 2004). These complexes reinforce transversely inter laced structures of the cell wall, thereby stabilizing them.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of probable mechanisms accounting for the activating effect of boric acid on HM removal from the soil by plants is that boron is involved in complexation with carbohydrate derivatives, pectin and rhamnoga lacturonan II, in the cell wall (Kobayashi, Matoh, and Junichi, 1996;O'Neill et al, 1996), with the resulting complexes also including metal ions such as Ca 2+ , Sr 2+ , Ba 2+ , Pb 2+ , and La 3+ (Matsunaga and Ishii, 2004). These complexes reinforce transversely inter laced structures of the cell wall, thereby stabilizing them.…”
Section: Resultsmentioning
confidence: 99%
“…The role of boron in plants is being actively studied. It has been shown that it is involved in structural organization of the cell wall (Kobayashi, Matoh, and Junichi, 1996;O'Neill et al, 1996;Matsunaga and Ishii, 2004) and has an effect on ion transport through membranes (Blaser Grill et al 1989;Ferrol and Donaire, 1992;Cakmak, Kurz, and Marschner, 1995;Wang et al, 1999).…”
mentioning
confidence: 99%
“…The flow-injection conditions were as follows: carrier, deionized water; flow rate, 1.0 mL/min; and injection volume, 20 μL. 15,19 The residue extracted with deionized water, as described above, for the determination of water-soluble B was suspended in 800 μL of aqueous 80% (v/v) ethanol, mixed by a homogenizer POLYTRON PT1300D (KINEMATICA, Lucerne, Switzerland), shaken for 20 min and centrifuged. The residue was then washed with 80% (v/v) ethanol, 99.5% (v/v) ethanol, chloroform:methanol (1:1, v/v), acetone and deionized water, freeze-dried, and used as a cell-wall sample.…”
Section: Determination Of Total and Water-soluble Boron In Tissuesmentioning
confidence: 99%
“…8,11 Waterinsoluble B has been revealed to exist in cell walls as a dimeric rhamnogalacturonan II-borate (dRG-II-B) complex, in which a borate-apiose (1:2) ester cross-links two monomeric RG-IIs. [12][13][14][15][16] The pectic polysaccharide RG-II is covalently bound to homogalacturonan, which is a major component of pectin. 17 The borate cross-linked RG-II or dRG-II-B/total RG-II ratio in cell walls of B-sufficient and deficient plants is reported to be 0.8 -0.9 and 0 -0.2, respectively.…”
mentioning
confidence: 99%